Use Of Nerve Block In The Treatment Of Orofacial Pain: An Integrative Re- view Of The Literature. - Falcão, Stephanie Bezerra Muniz; Brito, Pedro Serra Galdino Farias De; Rodrigues, Ana Beatriz Rocha; Júnior, José Lima Silva; Duarte, Beatriz Diniz; Sales, Mariana Luna De; Martins, Larissa Pereira; Muniz, Nycolly Fernandes Porto; Silva, José Mateus Américo da; Farias, Ítalo de Lima; Andrade, Arthur Marques de; Xavier, João Mykael Alves; et al. (Headache Medicine, 2023)
Full abstract in PDF.